Η τεθλασμένη πρόσληψη της αρχαιοελληνικής ποίησης και το ποίημα «Πάνω σ’ ένα ξένο στίχο» του Γ. Σεφέρη - Πασχάλης, Μιχαήλ (Σύγκριση/Comparaison/Comparison, 2021)
Refracted Modern Greek reception of Ancient Greek poetry and George Seferis’ poem ‘Upon a Line of Foreign Verse’ The term ‘refracted’ describes instances where Modern Greek reception of Ancient Greek poetry is mediated through one or more intertexts, like Italian-Latin or French-Latin. After treating briefly Dionysios Solomos’ poem ‘The Shade of Homer’ (1821-1822) the paper focuses on George Seferis’ ‘Reflections on a Foreign Line of Verse’ (1931). Each of the two poets claims the Homeric heritage for himself as a Greek poet through a poem that constitutes a refracted reception of Homer. The former opens a chain of three literary windows one after the other: first the appearance of Homer to the character Ennius in Petrarch’s Latin epic Africa; next Cicero’s ‘Dream of Scipio’; and finally the appearance of Homer to the Latin poet Ennius, who in the proem of his Annals represented himself as a reincarnation of the Greek poet. In responding to Solomos about a hundred years later Seferis treated the subject of Homeric Odysseus’ sea wanderings by commenting on ‘Heureux qui, comme Ulysse, a fait un beau voyage’, the opening line of Joachim du Bellay’s famous sonnet XXXI of the collection Les regrets (1558). Most probably Bellay reached back to Homeric Odysseus through a passage of Ovid’s collection of elegies written in exile and entitled Ex ponto. Ovid conceived his banishment from Rome to a region of modern Romania as the analogue of Odysseus’ wanderings away from Ithaca and became a source of inspiration for Du Bellay and other poets.